2022
DOI: 10.3390/antibiotics11070841
|View full text |Cite
|
Sign up to set email alerts
|

Acetylome and Succinylome Profiling of Edwardsiella tarda Reveals Key Roles of Both Lysine Acylations in Bacterial Antibiotic Resistance

Abstract: The antibiotic resistance of Edwardsiella tarda is becoming increasingly prevalent, and thus novel antimicrobial strategies are being sought. Lysine acylation has been demonstrated to play an important role in bacterial physiological functions, while its role in bacterial antibiotic resistance remains largely unclear. In this study, we investigated the lysine acetylation and succinylation profiles of E. tarda strain EIB202 using affinity antibody purification combined with LC-MS/MS. A total of 1511 lysine-acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…K6, K38, K83, K107 and K120 were identified as acetylated residues in both media. Combining the previously identified acetylated K96 in E. piscicida acetylomics ( 29 ), the total lysine acetylation sites of E. piscicida are indicated by red arrows, while the lysine acetylation sites of E. coli are indicated by orange arrows ( 21 ) ( Supplementary Figure S4D ). Both E. piscicida and E. coli had lysine acetylation at the K6, K57, K83, K87, K96, K107 and K120 sites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…K6, K38, K83, K107 and K120 were identified as acetylated residues in both media. Combining the previously identified acetylated K96 in E. piscicida acetylomics ( 29 ), the total lysine acetylation sites of E. piscicida are indicated by red arrows, while the lysine acetylation sites of E. coli are indicated by orange arrows ( 21 ) ( Supplementary Figure S4D ). Both E. piscicida and E. coli had lysine acetylation at the K6, K57, K83, K87, K96, K107 and K120 sites.…”
Section: Resultsmentioning
confidence: 99%
“…In E. piscicida , H-NS acts as an inhibitor of both the T3SS and T6SS and is expelled by the countersilencing protein EnrR during infection ( 9 ). In addition, acetylomics analysis of E. piscicida identified 1511 lysine acetylation sites on 589 proteins, which are predominantly involved in the tricarboxylic acid cycle, pyruvate metabolism and antimicrobial resistance pathways ( 29 ). Here, we characterized H-NS as a lysine acetylation protein and identified its acetyllysine sites under favorable amino acid nutrition conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The protein acylation field in bacteria has exploded since 2008. The acetylomes of more than 50 different species are now available, with catalogs of hundreds of proteins, reviewed here and previously. In addition, other acyl modifications are being identified and continually studied in bacteria, including succinylation, ,,,, malonylation, ,, and propionylation. As we continue to discover more PTMs, the need to understand their physiological relevance becomes greater. It is important to note that among acylome studies there is a large variation in modified sites and proteins that are identified, often with little overlap between studies, even for the same species.…”
Section: Perspectivesmentioning
confidence: 99%
“…The overuse of antibiotics has resulted in high rates of antibiotic resistance, especially to ampicillin and oxytetracycline. In E. tarda , 589 proteins were acetylated and 692 proteins succinylated . Interestingly, antibiotic resistance genes, such as efflux pumps, porins, and drug targets, were frequently acylated, suggesting a role of these modifications in the regulation of resistance traits.…”
Section: Proteomic Contributions To Our Understanding Of Ptm Crosstalkmentioning
confidence: 99%
See 1 more Smart Citation